Desenvolvimento e avaliação de estratégias educativas para combater a Dengue, Zika e Chikungunya no ensino fundamental II - Ferreira, Fernanda Abraão (2017)
The present work presents a proposal for the development and evaluation of educational strategies aimed at the teaching of arboviruses of major importance for public health at present: Dengue (DEN); Zika Virus (ZIKV); And Chikungunya (CHIK), aiming to increase the perception of elementary school students regarding the biological and clinical aspects of these viruses. The educational strategies were applied to the students of the 7th and 8th years of elementary school of the Santo Antônio State College (CESA), located in the fourth district (Xerém) of Duque de Caxias, RJ. The three teams were formed with up to 5 students in which the game "Mosquito Hunt" was applied with questions of easy, medium and difficult levels, with categories of epidemiology and etiology - EP / ET; Signs and symptoms - SS; Transmission - TR; And prevention - PR. The team that finished the game first was the winner. After the game the participants were directed to the contextualization of the theme, through lecture and in the end they received the educational booklet. Later, in a period of 30 days, it was returned to the CESA for reapplication of the game "Mosquito hunting", for the same group of students, being used other questions. Then, we analyzed the scores and observed that DEN and ZIKV had a greater number of hits than CHIK, during the project, it was analyzed that the use of educational interventions can promote the sensitization of the students to the information related to these arboviroses favoring them to become dispersers of this information in their environment.